Methods of Measuring Success in Polish Start-ups - Majewski, Marcin (Metody pomiaru sukcesu w polskich start-upach, 2025)
Aim: The aim of this article was to identify possible methods for measuring success in start-ups and their classification. Other goals included examining what situations indicate success or failure for selected Polish start-ups and how their success is measured. Methodology: In order to reach the stated objective, a body of literature was analysed and empirical study conducted. A survey was carried out among start-up enterprises in Poland. Results: The first method of evaluation of a startup’s success is the financial assessment, which involves measuring success based on factors, such as profitability, growth, and financial objectives. The second method focuses on non-financial indicators of startup success, which encompass aspects including reputation, networking, personal and customer satisfaction, and competitive positioning. An intermediate indicator that falls between these two categories is the startup’s ability to survive in the market. It was found that the greatest success of start-ups in Poland, is determined by the company’s survival on the market. Implications and recommendations: It is possible to compare the perception of success in start-ups in selected regions of the world and examine how they measure the achievements of their enterprises. Originality/value: The paper is an important contribution to the subject literature, because so far the methods of measuring success in Polish start-ups have not been comprehensively examined.
Ekonomia XXI Wieku = Economics of the 21st Century, 2025, Nr 28, s. 9-17
Keywords: start-up; success; entrepreneurship; sukces; przedsiębiorczość